PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI PESANTREN MTI CANDUANG - Aldri Aldri; Zulfani Sesmiarni; Supratman Dzakir; Rafiqa Witri Asri; Ali Mustopa Yakub Simbolon; Ulmadevi Ulmadevi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
The aim of this research is to investigate the impact of motivation and work discipline on teacher performance at MTI Canduang Islamic Boarding School. The study utilized a quantitative descriptive approach, with a sample size of 50 respondents selected through a questionnaire survey. The findings of the study revealed the following: 1) work motivation significantly influences teacher performance, 2) work discipline has a significant impact on teacher performance, and 3) there is a significant relationship between work motivation, work discipline, and teacher performance. The R2 analysis yielded a coefficient of determination (R2) value of 0.534 or 53.4%. This indicates that 53.4% of the variation in teacher performance at MTI Canduang can be explained by the independent variables of work discipline and work motivation. Furthermore, it was found that 33.1% of teacher performance at MTI Canduang is influenced by factors not considered in the research model.